Afrocentric architecture for lowcost housing design in Kano, Nigeria: exploring opportunities/ Aisha Abdulkarim Aliyu and Alice Sabrina Ismail - Abdulkarim Aliyu, Aisha; Ismail, Alice Sabrina (Universiti Teknologi MARA, Perak, 2023)
Afrocentric architecture for low-cost housing is a sustainable, economic, and cultural solution that can be used to address the housing needs of lowincome communities in Kano, Nigeria. Low-cost housing is a critical need in many developing countries, including Nigeria, where rapid urbanization and population growth have led to a shortage of affordable and sustainable housing options. This paper explores the concept of Afrocentric architecture for low-cost housing design in Kano Nigeria, with a focus on the sustainable, economic, and cultural benefits of this approach. The paper begins by providing background information on low-cost housing design in Kano Nigeria and discussing the importance of Afrocentric architecture in this context. The study employs a qualitative approach, case studies, interviews, and Observation, to identify key principles of Afrocentric architecture that can be incorporated into low-cost housing design in Kano, Nigeria. The limited integration of Afrocentric architecture principles in low-cost housing design in Nigeria has led to a disconnect between cultural heritage and contemporary design practices and hindered the potential economic, social, and environmental benefits of sustainable housing design. In addition, it discusses the economic benefits of Afrocentric architecture for low-cost housing design, including how it can create jobs, stimulate local economies, and reduce construction costs. The paper explores the cultural benefits of Afrocentric architecture for low-cost housing design, including how it can preserve local culture and heritage, promote social cohesion and community building, and contribute to cultural development in Kano Nigeria. The study's findings provide important insights into the potential benefits of Afrocentric architecture for low-cost housing design in Nigeria and inform future design and policy decisions related to sustainable development, cultural preservation, and economic growth.